Dietary Intake of Polyunsaturated Fatty Acids Lowers the Risk of Osteoporosis in Older Korean Females (Central Asian Journal of Medical Sciences, 2020)
Objectives: Osteoporosis is an important issue because it is associated with the risk of fractures. However, there is no study in the Republic of Korea on the relationship between PUFAs and the osteoporosis prevalence in middle-aged Korean women using public data. Methods: We intend to prepare basic data for osteoporosis by analyzing the prevalence of osteoarthritis in 3,294 women aged over 50 based on demographic and nutritional characteristics using the 7th KNHANES data using multiple logistic regression. Results: In unadjusted logistic regression analysis, the group with higher than average daily intake of PUFA had a lower prevalence of osteoporosis than the group with lower PUFA intake. In the final model, after adjustment for demographic variables such as sex and age, the group with high PUFA intake had up to 20% lower prevalence of osteoporosis than the other group. However, the effect size in the adjusted and unadjusted models was increased. Conclusions: A higher consumption of omega-3 and omega-6 fatty acids than the average daily intake in Korean women ages 50 years and older was negatively correlated with osteoporosis prevalence. We infer that adequate intake of PUFAs such as omega-3 and omega-6 fatty acids may help prevent osteoporosis.